Ostrowski Type Inequalities for s-Convex Functions via q-Integrals. (20th January 2022) - Khan, Khuram Ali; Ditta, Allah; Nosheen, Ammara; Awan, Khalid Mahmood; Mabela, Rostin Matendo
Abstract : The new outcomes of the present paper are q -analogues (q stands for quantum calculus) of Hermite-Hadamard type inequality, Montgomery identity, and Ostrowski type inequalities for s -convex mappings. Some new bounds of Ostrowski type functionals are obtained by using Hölder, Minkowski, and power mean inequalities via quantum calculus. Special cases of new results include existing results from the literature.